Microbiology of acid waters ans ferruginous precipitates formation in the polish part of the Muskau Arch - preliminary raport = Mikrobiologia kwaśnych wód a tworzenie się żelazistych osadów w polskiej części Łuku Mużakowa - wstępne wyniki - Bożęcki, Piotr; Rzepa, Grzegorz; Ratajczak, Tadeusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This work presents preliminary results of mineralogical, geochemical and microbiological investigations carried out in the Polish part of the Muskau Arch. As a result of sulphide oxidation in this abandoned mining area, highly acidified Fe-rich waters have been formed. Ferruginous precipitates composed mainly of schwertmannite, goethite, jarosite and gypsum accompany them. Both the water chemistry and the rate of the sediments formation vary significantly due to seasonal weather changes and microbiological activity.
Keywords: kwaśne wody; osady żelaziste; Łuk Mużakowa; AMD environment; pyrite oxidation; Muskau Arch; schwertmannite; goethite; jarosite; microbiological variability